Are Consumer Durables Important for Business Cycles? - Baxter, Marianne (The Review of Economics and Statistics, 1996)
This paper investigates whether consumer durables are important for the generation and propagation of business cycles. The author constructs a two-sector model that succeeds in generating business cycles that mimic empirical patterns of cross-sector volatility and comovement. She finds that half the relatively higher volatility associated with the durable-goods sector is due to higher volatility of shocks hitting this sector, with the other half due to endogenous responses, notably the investment accelerator. Nevertheless, this model does not have stronger internal propagation than the one-sector model. Further, incorporating durable consumer goods has little effect on the behavior of other macroeconomic variables. Copyright 1996 by MIT Press.